2018
DOI: 10.5663/aps.v7i1.29326
|View full text |Cite
|
Sign up to set email alerts
|

Fertility of Aboriginal People in Canada: An Overview of Trends at the Turn of the 21st Century

Abstract: This paper aims to give an overview of trends regarding the fertility of Aboriginal people in Canada at the turn of the 21st century (mostly between 1996 and 2011). Total fertility rates and fertility rates by age group are presented for the Aboriginal population as a whole, but also for First Nations, Métis, and Inuit, as well as for the population with Registered Indian status, using various data sources (past censuses, National Household Survey, vital statistics, and Indian Register). Results of a multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Migration into and from reserves during this period contributed to an increase in the mean age of this population by 0.7 years; i.e., the mean age would have increased by 0.3 years had there been no migration. 27 This may seem surprising but the relatively high fertility rates observed on reserves, with a total fertility rate way above the replacement level at around three children per woman (Morency et al 2018), explain why the population is continually growing, with younger cohorts surpassing older ones. This growth factor contributes to the rejuvenation or maintenance of the young age structure of the population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Migration into and from reserves during this period contributed to an increase in the mean age of this population by 0.7 years; i.e., the mean age would have increased by 0.3 years had there been no migration. 27 This may seem surprising but the relatively high fertility rates observed on reserves, with a total fertility rate way above the replacement level at around three children per woman (Morency et al 2018), explain why the population is continually growing, with younger cohorts surpassing older ones. This growth factor contributes to the rejuvenation or maintenance of the young age structure of the population.…”
Section: Discussionmentioning
confidence: 99%
“…This represents an annual growth rate of 2.5%, which is close to twice the growth rate experienced in Canada over the same period (1.3%). A secular high fertility explains, in large part, this relatively high growth rate (Morency et al 2018). Several past studies based on censuses and the NHS (which replaced the long-form census questionnaire in 2011) showed that positive internal migration also contributed to the population growth of reserves (Cooke and Penney 2019;Cooke and O'Sullivan 2015;Norris and Clatworthy 2011;Norris 2007, 2014;Norris et al 2004;Norris 1990Norris , 1996Norris , 1985, although these results seem to be largely caused by the limitations of using retrospective information for measuring migration flows from or toward reserves.…”
Section: Short Review Of Past Studiesmentioning
confidence: 99%
“…The population of Indigenous people in Canada is growing. By 2036, there is expected to be approximately 1.2 million Indigenous people in Canada (Morency et al , 2015). The Canadian workforce is moving towards increasing acceptance of Indigenous employees (OECD, 2018); however, the question of whether or not the workforce will adapt to provide Indigenous workers equitable access to employment remains.…”
Section: Mental Health In Indigenous Populationsmentioning
confidence: 99%
“…First Nations populations also experience limited access and prohibitive barriers to health and healthcare services ( FNIGC, 2018 ; Slater et al, 2020 ). This is especially relevant as the population of older First Nations people in Canada is expected to dramatically increase, with those aged 65 and over expected to nearly triple in number by 2036 ( Morency et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%